2017
DOI: 10.1002/er.3885
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a novel hybrid solar photovoltaic/wind system to maintain the cell surface temperature and to generate electricity

Abstract: Summary A hybrid solar photovoltaic/wind system is proposed and investigated theoretically. The hybrid system is based on attaching a converging inclined duct beneath the photovoltaic (PV) panels and directed upward after the end of the panels. A wind turbine is attached at the exit of the converging duct. The converging duct will capture wind currents that at its inlet and enhances these current by buoyancy effect created by the rejected heat from the panels. The mixed convection air flow is used in cooling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…[95][96][97][98] On the other hand, high temperature causes to reduce the generated power because of increasing internal resistance of solar cells. [95][96][97][98] On the other hand, high temperature causes to reduce the generated power because of increasing internal resistance of solar cells.…”
Section: Square Cells Circular Solar Imagementioning
confidence: 99%
See 1 more Smart Citation
“…[95][96][97][98] On the other hand, high temperature causes to reduce the generated power because of increasing internal resistance of solar cells. [95][96][97][98] On the other hand, high temperature causes to reduce the generated power because of increasing internal resistance of solar cells.…”
Section: Square Cells Circular Solar Imagementioning
confidence: 99%
“…Adopted from Al-Nimr et al 130 with permission from Elsevier | 317 KHATIBI eT Al. Adopted from Al-Nimr et al 130 with permission from Elsevier | 317 KHATIBI eT Al.…”
Section: Square Cells Circular Solar Imagementioning
confidence: 99%
“…This system is based on air cooling of the PVT. They indicated that proposed system could achieve to decrease the PV cell temperature and to produce additional electricity by the turbine in the simulation results . In their another study, Sharadga et al presented a novel hybrid system that uses the cooling water of a concentrated PV/T as a preheated water for lithium bromide‐water–based Kalina cycle.…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges of the solar still is the difficulty of the condensation process of the water vapor. To enhance the condensation process, these techniques have been studied: (a) cooling of the glass cover by the flow of air and water and air, (b) enlarging the condensation area, (c) condensation by finned coupled condenser, and (d) active cooling by incorporating TEC …”
Section: Introductionmentioning
confidence: 99%